Artificial intelligence as a socio-technical system in business school environment from students’ perspective : Case Turku School of Economics - Kemppainen, Lauri (My University, 2025)
Artificial intelligence (AI) and various tools utilising it have become more and more popular during the last few years. With the number of tools increasing their availability, has also become better, and many new usages have been found. AI tools have found their way in higher educational environments as well with students using them in different ways. Previous studies regarding AI use in higher education environments regard AI mainly as a technology that affects education, but it should also be seen as a change force affecting pedagogical, ethical, social, cultural, and economic aspects of education. Therefore, in this thesis socio-technical system theory, chosen as the framework, gives a perspective that regards AI as a system that next to the technical aspects considers the social aspects and the environment in which the system is embedded in, equally important. AI has been previously identified as a socio-technical system. Socio-technical systems framework used in this study was originally designed to give proper guidelines to map and analyse these complex systems. However, this specific framework has been previously used mainly in a business context but interest for broadening the environments where it is used has also been stated. The aim of this thesis is to find out how AI appears as a socio-technical system in the context of business school studies in order to clarify students’ perceptions on AI’s effect on higher education studies. As the case context for this Turku School of Economics was chosen to get more rigid data with less uncontrollable variables. By gathering data from interviews with business school students from Turku School of Economics and analysing it with theory-driven thematic analysis, different themes explaining this system were found. Major findings include the following: 1) the ways in which AI is used by students 2) the effect that AI has to social dynamics 3) the lack of quality in the regulations regarding AI use in studies 4) the challenges it provokes according to the interviewed students. This thesis takes part in the recent discussion on AI use in higher education environments as well as gives new basis for future studies regarding AI as a socio-technical system. This thesis also answers to the call on expanding the use of this particular framework with it successfully implemented in this context.
Keywords: Artificial intelligence, Socio-technical systems, AI in higher education.